SOSIALISASI HIDUP SEHAT SEJAK DINI : EDUKASI ISI PIRINGKU BAGI SISWA KELAS V SD YAYASAN PRAYOGA PADANG - Reny Salim; Tuty Taslim; Verawaty Verawaty; Irene Puspa Dewi; Fita Selonni (Fakultas Teknik, Universitas Bangka Belitung, 2023)
Many children or adolescents still suffer from imbalances in nutritional intake. The Indonesian government, in particular, has created an educational program,